Certain questions awaiting answers in the foreign language classroom - Kateryna Lizak; Лізак Катерина; Lizák Katalin (Національний технічний університет України «Київський політехнічний інститут», 2013)
Abstract. The present article is based partly upon the study of relevant academic literature but is mainly the result of teaching practice of English as a foreign language at different levels with a variety of age groups, and aims at sharing certain ideas to consider and discuss while working in a forerign languge classroom. In addition, an attempt will be made to reflect on some aspects of the English language education from a different perspective, namely shifting the emphasis from the method of teaching to the material of instructing, i.e. from how to tech to what to teach.
Keywords: method of teaching; material of instructing; collocations; language teaching classroom; foreign language instruction